Grammatical Errors in English Job Advertisements - Monica Monica; Magdad Hatim; Santi Mayasari (Jurnal Pendidikan Bahasa, 2023)
The researcher aimed to identify the types of grammatical errors and the frequencies and percentages of each type of grammatical error. The method of this research was qualitative descriptive. The data of the research were taken from fifteen job advertisement texts of document publications, namely JS. The data analysis used the theory from Creswell that there were seven steps in analyzing errors which included: organizing and preparing the data analysis, reading all the data, starting coding all of the data, using the coding process to generate a description of the setting as well as categories for analysis, quantifying the errors, and interpreting the description, and drawing a conclusion. The errors found in the fifteen English job advertisement texts, there were four types of errors with the frequencies and percentages of each type of grammatical error. There were 250 errors made by advertisement text writers. The errors were 91 items (36.4%) of omission errors, 20 items (8.0%) of addition errors, 138 items (55.2%) of misformation errors, and 1 item (0.4%) of misordering errors. The result of the research could be used as input to avoid further errors.Â Â